Answer:
Style A shoes sold : <u>152</u>
Style B shoes sold : <u>88</u>
Step-by-step explanation:
Let :
- Style A shoes = x
- Style B shoes = y
Forming equations :
- x = 2y - 24
- 66.95x + 84.95y = 17,652
Substitute the value of x from 1 in 2.
- 66.95 (2y - 24) + 84.95y = 17,652
- 133.90y - 1606.80 + 84.95y = 17,652
- 218.85y = 19258.80
- <u>y = 88</u>
<u />
Finding x :
- x = 2(88) - 24
- x = 176 - 24
- <u>x = 152</u>
<u />
Solution :
- Style A shoes sold : <u>152</u>
- Style B shoes sold : <u>88</u>
The equivalents of the given compound inequality are x > 3 and x ≤ 5.2 OR 3 < x ≤ 5.2
<h3>Solving inequalities </h3>
From the question, we are to determine the equivalent form of the compound inequality
We will solve the given compound inequality
The given inequality is
−22 > −5x − 7 ≥ −33
We can write that
−22 > −5x − 7 AND −5x − 7 ≥ −33
Solving −22 > −5x − 7
5x > -7 +22
5x > 15
x > 15/5
x > 3
Also,
Solve −5x − 7 ≥ −33
−5x ≥ −33 +7
-5x ≥ -26
x ≤ -26/-5
x ≤ 5.2
Hence, the equivalents of the given compound inequality are x > 3 and x ≤ 5.2 OR 3 < x ≤ 5.2
Learn more on Inequalities here: brainly.com/question/20356565
#SPJ1
I think that the answer is 226.194 inches
Answer:
1. ![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
2. ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
3a. ![-\frac{1}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B4%7D)
3b. 3
3c. ![-\frac{4}{5}](https://tex.z-dn.net/?f=-%5Cfrac%7B4%7D%7B5%7D)
4. ![m = \frac{y_1 - y_2}{x_1-x_2}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_1%20-%20y_2%7D%7Bx_1-x_2%7D%5C%5C)
Step-by-step explanation:
1.
Rises 6 inches for every horizontal change of 16 inches
Slope = rise/run
Slope = 6/16
Slope = 3/8
2.
Rises 3 feet for every horizontal change of 12 feet
Slope = rise/run
Slope = 3/12
Slope = 1/4
3a.
![m = \frac{y_1 - y_2}{x_1-x_2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_1%20-%20y_2%7D%7Bx_1-x_2%7D)
![m = \frac{3-2}{-2-2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B3-2%7D%7B-2-2%7D)
![m = \frac{1}{-4}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B1%7D%7B-4%7D)
![m = -\frac{1}{4}](https://tex.z-dn.net/?f=m%20%3D%20-%5Cfrac%7B1%7D%7B4%7D)
3b.
![m = \frac{y_1 - y_2}{x_1-x_2}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_1%20-%20y_2%7D%7Bx_1-x_2%7D%5C%5C)
![m = \frac{-1 - 2}{-1-0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-1%20-%202%7D%7B-1-0%7D)
![m = \frac{-3}{-1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B-3%7D%7B-1%7D)
![m = 3](https://tex.z-dn.net/?f=m%20%3D%203)
3c.
![m = \frac{y_1 - y_2}{x_1-x_2}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_1%20-%20y_2%7D%7Bx_1-x_2%7D%5C%5C)
![m = \frac{1 - (-3)}{-1-4}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B1%20-%20%28-3%29%7D%7B-1-4%7D%5C%5C)
![m = \frac{4}{-5}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B4%7D%7B-5%7D%5C%5C)
![m = -\frac{4}{5}](https://tex.z-dn.net/?f=m%20%3D%20-%5Cfrac%7B4%7D%7B5%7D)
4.
![m = \frac{y_1 - y_2}{x_1-x_2}\\](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_1%20-%20y_2%7D%7Bx_1-x_2%7D%5C%5C)
Answer:
I am pretty sure it is d, if i am wrong, I am sorry.
Step-by-step explanation:
?